2001
DOI: 10.1002/qua.1326
|View full text |Cite
|
Sign up to set email alerts
|

Nitrenes as intermediates in the thermal decomposition of aliphatic azides

Abstract: N 2 extrusion from hydrazoic acid, methyl azide, and ethyl azide to yield the corresponding nitrene has been studied with high-level ab initio calculations. Geometry optimizations of stationary points and surfaces crossing seams were carried out with the complete active space self-consistent field (CASSCF) method, and their energies were reevaluated with the second-order multireference perturbation (CASPT2) theory and corrected by the zero-point energy (ZPE). The analytic harmonic frequencies calculated at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 42 publications
4
36
1
Order By: Relevance
“…For the simplest azide, hydrazoic acid, the mechanistic picture emerging from experiment and theory is now fairly consistent, as discussed below. [10][11][12][13][14][15] For organic azides, including the simplest member of the series, CH 3 -N 3 , the picture is somewhat less clear. [16][17][18][19] In particular, there remains significant controversy regarding the role of open-shell triplet state intermediates following the extrusion of dinitrogen from the parent singlet species.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…For the simplest azide, hydrazoic acid, the mechanistic picture emerging from experiment and theory is now fairly consistent, as discussed below. [10][11][12][13][14][15] For organic azides, including the simplest member of the series, CH 3 -N 3 , the picture is somewhat less clear. [16][17][18][19] In particular, there remains significant controversy regarding the role of open-shell triplet state intermediates following the extrusion of dinitrogen from the parent singlet species.…”
Section: Introductionmentioning
confidence: 96%
“…Other studies reached similar conclusions, 14 although it was also noted that the relatively small difference in barrier heights was consistent with the observation of both singlet and triplet products. 15 Early experiments on the pyrolysis of methyl azide in the gas phase showed that it was a unimolecular reaction, 21,27 which produces nitrogen, hydrogen, and HCN, 27,28 as well as methyleneimine CH 2 NH. 29 The activation energy was reported in 1933 by Leemarkers as about 43.5 kcal/ mol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of research has been carried out to assign the microwave, infrared, and electronic spectrum of this moiety [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. As a reactive species, MI can dissociate by 1,2-elimination of H 2 which has been studied both experimentally and theoretically [44][45][46][47][48][49][50][51][52][53][54][55]. Vinylamine and ethyleneimine are chemicals that widely used in industry; they were first detected as primary pyrolysis product of EA in the gas phase using microwave spectroscopic technique by Lovas et al [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The most thoroughly studied nitrenes are amidogen NH 6 and phenylnitrene C 6 H 5 N. 7 In contrast to aromatic nitrenes, much less is known about alkylnitrenes such as CH 3 -N, CH 3 CH 2 -N, ͑CH 3 ͒ 2 CH-N, and ͑CH 3 ͒ 3 C-N. Even basic physical and chemical data, such as ionization energies, are not available for nitrenes yet.…”
Section: Introductionmentioning
confidence: 99%